CLINICAL EVALUATION OF Paragonimiosis IN CATS EXPERIMENTALLY INFECTED WITH Paragonimus mexicanus - Gallardo V., Christina (2014)
The objective of this study was to describe the clinical signs associated to theexperimental infection of Paragonimus mexicanus in cats. Eight cats of 2.5 to 4 months ofage were orally infected with 7 to 20 metacercariae. In the physical examination during theacute phase was found fever, wet cough, and enlargement of the inguinal lymph node,while in the chronic phase wet cough, positive tracheal reflex and increase of the breathsound. On the complete blood count was found leukocytosis with different degrees oflymphocytosis, neutrophilia and eosinophilia in the acute phase and leukocytosis withan increase of eosinophilia in the chronic phase. On the ultrasonography examination,enlargement of the vesicular wall, hepatomegaly, splenomegaly and increase in liverechogenicity were found, especially during the acute phase. The early radiological findingsincluded bronchiectasis focus, bronchial thickening and increased radiopacity of lunglobes, while in the chronic phase radiopaque ovoid structures in the pulmonary parenchymaand bronchiectasis were observed. The period between infection and presence of P.mexicanus eggs in the faeces was between 41 and 71 days. The necropsy confirmed thepresence of cysts and parasites in the lungs.